Design of a Sustainable City in Iraq Using SAM Program to Calculate Renewable Energy - Al-Swaiedi, Safaa J.; Altmimi, Amani I.; Al-khalidi, Aamar A. (Iraqi Journal of Science, 2021)
Urban design and human activity are main causes of environmental pollution and climate change, such as reliance on energy production plants, factories and transportation that depend on fossil fuels, in addition to transformation of most green areas into residential areas. This paper aims to establish a sustainable city with an environment friendly urban design that contributes to exploitation of natural resources in the generation of electric power, use of green means of transport and thus the reduction of pollution. Anah site was chosen as the best site for designing a sustainable city, with its natural resources, air quality and moderate climate. The total area of ​​the city is 9990187m2 divided into seven main parts, which include residential area, green areas, agricultural areas, public areas, wind farm, industrial area, and solar collecting area. SAM software has also been used in the city’s renewable energy accounts. It was found that the annual output of the wind farm consisting of 15 turbines is 71080608 kWh and the power factor ratio is 36.1%. While the annual production of solar energy for each house was equal to 12527 kWh and the power factor was 23.8%.